Codification of director's duties into statutory statements : whether proposed statements accurately captures the common law duties. - Lim, Boon Lan. (2008)
In the context of the recent proposal for the codification of director duties in Singapore, this project seeks to investigate: firstly, the feasibility and soundness of the translation of general laws into statutes, and secondly, to examine whether the 9 proposed statements by the CLRFC accurately capture the general law positions. We looked into the five key duties of director under the general laws and examined whether the 9 proposed statements of CLRFC accurately capture aspects of the duties. In addition, we have also assessed the reasons for and against codification. Our study has revealed that not all the statements capture the five key duties in a precise manner. Some of the problems include the absence of explicit requirements constituting the minimum standard of care, presence of some subtle but significant divergences from the general law duty and repetition of the. These incongruences can be refined, especially in the light of the recent release of the final United Kingdom Reform Bill. In spite of this, we are in favor of codification because the merits of codification (i.e making the law more consistent, comprehensible, certain and accessible) can be fully realized when such flaws are rectified.